2018
DOI: 10.1080/00222895.2018.1468310
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Postural Control: Comparing Expert and Intermediate Dancers

Abstract: The expert-novice approach is inappropriate for studying postural control in sport and dance when novices are completely unable to perform relevant postural tasks and experts cannot demonstrate specific skills on everyday postural tasks. We tested expertise-specific differences on 6 static everyday and 5 dynamic dance-like postural tasks of varying difficulty in 13 professional and 12 intermediate nonprofessional dancers. Results showed a clear expert advantage on sway area for dance-like postural tasks, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…it did not involve the context in which the athletes are trained. These results are in line with previous ndings which investigated the effect of expertise on the non-ecological context of postural control (static balance) among judokas, surfers, and dancers (15)(16)(17)(18). Moreover, the differences between elite ju-jitsu athletes and controls were observed in the so-called ecological conditions introduced in the present study as the ju-jitsu CS.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…it did not involve the context in which the athletes are trained. These results are in line with previous ndings which investigated the effect of expertise on the non-ecological context of postural control (static balance) among judokas, surfers, and dancers (15)(16)(17)(18). Moreover, the differences between elite ju-jitsu athletes and controls were observed in the so-called ecological conditions introduced in the present study as the ju-jitsu CS.…”
Section: Discussionsupporting
confidence: 92%
“…This was observed in lower values of COP range and rms. Many previous reports associated smaller postural sway with better postural skills (17,18,(28)(29)(30)(31). For example, ballet dancers exhibited lower values of COP area, range, and rms than non-dancers in a feet con guration represented the ballet-speci c position (18).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These authors reported that the more the postural tasks are specific and difficult, the more the athletes’ postural performance can be related to their competition level. Other works corroborate this principle since dance-like postural tasks have made it possible to discriminate expert dancers from intermediate dancers while this was not possible though static postural tasks (Munzert et al, 2018). Paillard et al (2011) observed that surfers at national and international competition levels were distinguished from surfers at local competition level when using dynamic postural tasks carried out on an unstable support (very close to the postural condition implied by surfing) but not when using static postural tasks completed on a stable support.…”
Section: Postural Performance and Sport Performancementioning
confidence: 85%